Prevalence, antibiogram, and cdt genes of toxigenic Campylobacter jejuni in salad style vegetables (Ulam) at farms and retail outlets in Terengganu - John Yew Huat, Tang; Mohd Ikhsan, Khalid; Nabila Huda, Baharuddin (2015)
The present study was conducted to investigate the prevalence and antibiotic resistance among Campylobacter jejuni in ulam at farms and retail outlets located in Kuala Terengganu, Malaysia. A total of 526 samples (ulam, soil, and fertilizer) were investigated for the presence of C. jejuni and the gene for cytolethal distending toxin (cdt) by using a multiplex PCR method. Antibiotic susceptibility to 10 types of antibiotics was determined using the disk diffusion method for 33 C. jejuni isolates. The average prevalence of contaminated samples from farms, wet markets, and supermarkets was 35.29, 52.66, and 69.88%, respectively. The cdt gene was not detected in 24 of the 33 C. jejuni isolates, but 9 isolates harbored cdtC. Antibiotic resistance in C. jejuni isolates was highest to penicillin G (96.97% of isolates) followed by vancomycin (87.88%), ampicillin (75.76%), erythromycin (60.61%), tetracycline (9.09%), amikacin (6.06%), and norfloxacin (3.03%); none of the isolates were resistant to ciprofloxacin, enrofloxacin, and gentamicin. In this study, C. jejuni was present in ulam, and some isolates were highly resistant to some antibiotics but not to quinolones. Thus, appropriate attention and measures are required to prevent C. jejuni contamination on farms and at retail outlets.